From educational ideals to local realities: qualitative unpacking of stereotypes and segregation in PISA 2006 - Fonseca, Pedro Moreno da (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2012)
Education is seen as being caught between the material-symbolic networks of schoolrelated agents and of students. The fundamental hypothesis of the research is that the scientific school-agents network is socioeconomically and ethnically biased, creating ontological insularization that is reflected both by structural variables in PISA surveys and by qualitative evidence from classroom interaction. On the other hand, it is explored the parallel hypothesis that social economic and cultural groups establish resilient identities whenever their expression and understandings are not enabled in a way that is translatable into the scientific network. Idealisations, steretypification processes, class, ethnicity and gender are explored as factors concurring to explain 9th graders performance. PISA 2006 data on cognitive science testing is firstly explored (Portuguese sub-sample, n=5100) through a multilevel model and then tentatively unpacked through case-study results from a research developed in a school. In conclusions, introduction of ontological adaptation and cultural variety to curricula and teaching methods are seen as fundamental to bridge the tendency to resistance in learning and separation between symbolic networks.